Ties that bind: The kin system as a mechanism of income-hiding between spouses in rural Ghana - Carolina Castilla (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
I present a model of intra-household allocation to show that when income is not perfectly observed by both spouses, hiding of income can occur even when revelation increases bargaining power. I draw data from Ghana and exploit the variation in the degree of asymmetric information between spouses, measured as the difference between the husband's own reporting of farm sales and the wife's reporting of his farm sales, to test whether the allocation of resources is consistent with hiding. Findings indicate that allocations are suggestive of men hiding farm sales income in the form of gifts to extended family members.
Keywords: D13; D82; J12; 330; incomplete information; income-hiding; non-cooperative family bargaining